The Relationship between Personality and Academic Burnout: Exploring the Influence of Psychological Well-Being and Demographic Factors - Wahyuni, Sri; Agustina, Hellya; Munthe, Ricca Angreini (International Journal of Islamic Educational Psychology, 2023)
Previous studies have found that academic burnout occurred at all levels of education, including universities. Academic burnout is characterized by emotional exhaustion, depersonalization, and a lack of confidence in students' abilities. Various variables can influence it, such as personality, well-being, and demographic factors. This research uses a correlational design to examine the relationship between personality and academic burnout among college students while exploring the role of psychological well-being as a mediator and demographic factors as a moderator. This design allows for the simultaneous collection of data from many individuals. We recruited 522 undergraduate students to participate in an online survey and used the Maslach-Student Burnout Inventory (MSBI), NEO Five-Factor Inventory (FFI), and Psychological Well-being Questionnaire for measurement. For data analysis, we used SPSS  version 25 and IBM SPSS AMOS version 24 to determine the mediation-moderation effect and tested the factor analysis of the proposed model. This research found a relationship between personality and academic burnout, with extraversion, agreeableness, conscientiousness, and openness to experience associated with low academic burnout. In contrast, neuroticism was associated with high academic burnout. Furthermore, the level of student psychological well-being was found to mediate the correlation between personality and academic burnout. Therefore, this study recommends that students, teachers, and parents pay attention to the importance of psychological well-being.